Survival Strategies of City Transportation Drivers In Purwokerto Banyumas Regency - Putri Nur Aini; Lilis Siti Badriah (EKO-REGIONAL, 2020)
According to the Central Statistics Agency (2017), the proportion of workers in the Indonesias informal sector is 57.03 percent in 2017. One of the jobs in the informal sector is city transportation drivers. Purwokerto has a population of 263,501 people in 2017 spreading across four sub-districts. Population needs for transportation are served by city transportation. The existence of the Trans Jateng bus and the growing development of on-line transportation services have reduced consumer demand for urban transportation services. As a consequence, it had an impact on the income of city transportation drivers. This study aimed to analyze the income and consumption, the welfare of life, and survival strategies of city transportation drivers in Purwokerto in meeting their family needs. The total sample of 78 respondents was selected randomly. The analytical methods used in this study were tabulation, Average Propensity to Consume analysis, comparison between income and Decent Standar of Living in Banyumas Regency, and survival strategies using coping strategies. The results indicated that 51.3 percent of respondents had basic income smaller than other income; the basic income of 89.74 percent of respondents had not been able to meet family consumption, but based on family income, it was obtained that 69.23 percent of respondents has been able to meet family consumption; both of basic income and family income of the majority of drivers have not been able to meet a Decent Standard of Living; the survival strategies used by the respondents were active, passive, and network strategies. This study implies that the Regional Government needs to adopt a policy that supports the city transportation drivers in the form of limiting the number of on-line transportations and monitoring the red zones as well as regulating the Trans Jateng Bus lane so that it may not have a negative impact on the city transportation.